Cultural tightrope walkers: a qualitative study of being a young refugee in quest for identity and belonging in Norway - Per-Einar Binder; Hanna Heggen; Elisabeth Buer Vase; Gro Mjeldheim Sandal (BMC Psychology)
Abstract Background Refugee experiences significantly challenge personal identity, especially for youth orienting themselves in new cultural contexts. The study explores the complex process of balancing expectations from two cultures: how do formative encounters in Norway mold the self-perception and sense of belonging of those who arrived as child and adolescent refugees? Methods A qualitative approach in which life story interviews were conducted with eight young refugees who arrived in Norway between the ages of 8 and 17 years was used. Through thematic analysis grounded in hermeneutical phenomenology, we analyzed their narratives to identify core experiences and perspectives. The interviews lasted 90–150 min, providing insights into personal identity development amid cultural adaptation. Results A recurring and overarching theme is that participants grapple with feelings of “outsiderness” both in Norwegian society and within their culture of origin, creating a dual sense of alienation. This experience is painful, but they also perceive that it has given them the opportunity to develop open-mindedness and a unique perspective on cultural existence. Three subthemes were identified that describe various aspects of these narratives in greater detail: (1) Experiences of being a stranger; (2) value conflicts, but value reconciliation is possible; and (3) a unique perspective: navigating between two cultures. The narratives highlight the complex negotiation between maintaining heritage and adapting to Norwegian norms. Conclusions The study of participants’ narrative identities reveals ways of coping with these transitions, revealing how participants continuously reconstruct their self-narratives to adapt to their new cultural environment. The findings suggest that while acculturation is a challenging process characterized by psychological tension and existential vulnerability, it can also foster personal resilience and new opportunities for meaning-making. The research contributes to understanding the refugee experience in Norway, emphasizing the need for social support systems that acknowledge both the struggles and potential for growth inherent in cultural integration.